2023
DOI: 10.1001/jamaoncol.2023.0089
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Alternative Dose Regimens of Exemestane in Postmenopausal Women With Stage 0 to II Estrogen Receptor–Positive Breast Cancer

Abstract: ImportanceSuccessful therapeutic cancer prevention requires definition of the minimal effective dose. Aromatase inhibitors decrease breast cancer incidence in high-risk women, but use in prevention and compliance in adjuvant settings are hampered by adverse events.ObjectiveTo compare the noninferiority percentage change of estradiol in postmenopausal women with estrogen receptor–positive breast cancer given exemestane, 25 mg, 3 times weekly or once weekly vs a standard daily dose with a noninferiority margin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Ingle et al, in a case-control study of postmenopausal women with early breast cancer, found that those with 0.5 pg/mL or higher serum estradiol after 6 months of adjuvant exemestane had a statistically significant 2.2-fold increase in early breast cancer–related events. Note that 0.5 pg/mL is below the 1-pg/mL limit of detection for the solid-phase extraction assay used for the primary analysis of the present study . In total, 69% of women in the daily-dose arm and 65% in the 3-times-weekly arm, but only 17% in the once-weekly arm, had estradiol suppressed below the 1-pg/mL detection limit.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Ingle et al, in a case-control study of postmenopausal women with early breast cancer, found that those with 0.5 pg/mL or higher serum estradiol after 6 months of adjuvant exemestane had a statistically significant 2.2-fold increase in early breast cancer–related events. Note that 0.5 pg/mL is below the 1-pg/mL limit of detection for the solid-phase extraction assay used for the primary analysis of the present study . In total, 69% of women in the daily-dose arm and 65% in the 3-times-weekly arm, but only 17% in the once-weekly arm, had estradiol suppressed below the 1-pg/mL detection limit.…”
mentioning
confidence: 67%
“…The authors suggest that the 3-times-weekly regimen should be studied further in longer-duration primary prevention and adjuvant therapy trials . Should we take their advice, given the inability to demonstrate noninferiority in the ITT analysis of the primary efficacy biomarker or difference in adverse events between the standard and 3-times-weekly arms?…”
mentioning
confidence: 99%
See 3 more Smart Citations